A phenomenological case study on immigrant workers' gambling addiction in Korea. Issue 2 (1st June 2019) - Kang, Sun Kyung; Shin, Seungnam
Abstract: This study explores the experiences that have led some of Korea's immigrant workers into gambling addiction and examines possible social welfare services that could support treatment. Immigrant workers' gambling experience as aliens in Korea was analyzed through the methodology of a phenomenological case study. The participants, who voluntarily consented to the study, were five immigrant workers addicted to gambling. Data were collected through one‐on‐one, in‐depth interviews over 6 months, starting in July 2018. The essential themes that emerged in the interviews were "changing strategies for survival, " "forgetting oneself without any sense of responsibility or shame, " "gambling as routine daily life, " "obsession with making a fortune in one go, " and "no home to return to." Based on its results, this study makes suggestions for the prevention of gambling addiction in immigrant workers. Further, future research needs to be broadened to analyze nationwide cases of immigrant workers with more diverse demographic backgrounds.